Introduction to social work and social welfare : - Zastrow, Charles (Cengage Learning, 2017)
The twelfth edition includes comprehensive Council on Social Work Education (CSWE) core content that aligns with the latest Educational Policy and Accreditation Standards (EPAS), as well as insightful coverage of new and emerging issues, making it the number one book for social work students.